[14C]-triolein absorption: a useful test in the diagnosis of malabsorption. Issue 6 (June 1987) - Turner, J M; Lawrence, S; Fellows, I W; Johnson, I; Hill, P G; Holmes, G K
Abstract : The [14C]-triolein absorption test has been assessed using a preprepared fat meal in a procedure that can be completed within a working day on an inpatient or outpatient basis. An initial study showed complete discrimination between 30 control subjects and 13 patients with raised faecal fat excretion. A prospective evaluation in 57 patients under investigation for gastrointestinal disease showed a sensitivity of 85% and specificity of 93% (100% if two obese subjects are excluded). The test discriminates satisfactorily between patients with and without fat malabsorption and makes the measurement of faecal fat unnecessary in most circumstances.